The Meanings of Fair Skin in Eight Unilever’s Skin-whitening Advertisements in Indonesia - Bella Tysha Gunawan; Jenny Mochtar (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Human skin color ranges from the darkest to the lightest. However, the culture and the power of media, especially advertisements, convince all women to embrace fair skin as the idealized self. This study aims to find how fair skin is represented in the selected eight Unilever’s skin-whitening advertisements and how this representation reflects consumerism. In conducting this study, I used the theory of representation and consumerism to find the symbolic meanings of consumerism. The finding showed that there were two meanings that are represented by the skin-whitening advertisements, such as youthfulness and success. In conclusion, those eight skin-whitening products were sold not just as products, but also as their symbolic meanings that lead women to youthfulness and success. Keywords: fair skin, skin-whitening advertisements, meanings, youthfulness, success, consumerism